Desain Mesin Pengolahan Sampah Plastik Menggunakan Teknologi Mesin Pencacah - Yohanes Viva Servianus; Abraham Donatus Baha; Dominikus Dionisius Fernandez (Pusat Riset dan Inovasi Nasional, 2024)
Plastic waste is a serious environmental problem because it does not decompose naturally and takes years to break down. To address this problem, an effective solution is to recycle plastic waste into economically valuable products. This study aims to design a plastic shredder machine using the Verein Deutscher Ingenieure (VDI) 2222 method. The machine is designed to improve the efficiency of plastic waste processing through faster and larger capacity shredding. The plastic shredder machine has specifications of 124 cm in height, 94.5 cm in length and 80 cm in width, with a frame made of 50x50x5 mm angle iron. It is equipped with 33 blades on two shafts, driven by a gasoline engine and capable of shredding plastic waste at a capacity of 31.5 kg/hour. The use of the VDI 2222 method ensures a structured and optimal design. The research results show that this machine is effective in reducing the volume of plastic waste and facilitating the recycling process.